Molecular modeling guided isotope separation of gadolinium with strong cation exchange resin using displacement chromatography. Issue 14 (22nd September 2017) - Boda, A.; Arora, S. K.; Singha Deb, A. K.; Jha, M.; Ali, Sk. M.; Shenoy, K. T.
ABSTRACT: Molecular modeling was carried out using DFT to identify the suitable displacing agent for carrying out Gd isotope separation using displacement chromatography. EDTA was identified as the best eluting agent among EDTA, malic acid and citric acid. Displacement chromatography of Gd adsorption band in cation exchange resin was performed to observe the isotope effects in the Gd ion exchange processes involving complex forming reagent – EDTA. The heavier isotope of 160 Gd was found to be enriched at the front boundary of Gd adsorption band, while the lighter isotopes of 155 Gd and 157 Gd were enriched at the rear boundary.